2014
DOI: 10.15280/jlm.2014.4.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Behavior Are Independently Associated with Weight in Korean Adolescents

Abstract: BackgroundThis study examines the relationship between physical activity (PA), sedentary behavior (SB) and body weight in Korean adolescents.Methods:This study used a nationally representative sample of 72,368 South Korean adolescents, aged 13 to 18 years. The study sample was categorized according to BMI as follows: underweight, body mass index (BMI) <18.5; normal weight, 18.5 ≤ BMI < 23.0; overweight, 23.0 ≤ BMI < 25.0; and obese, 25.0 ≤ BMI. An analysis was then performed to determine if meeting the recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(30 reference statements)
1
4
0
1
Order By: Relevance
“…Consistent with prior Western and South Korean singleton samples (e.g. Cho et al, 2014;Sallis et al, 2000), this study showed that the prevalence of vigorous exercise was higher in males than in females. This study further showed that sex difference was driven largely by differences in the extreme groups (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with prior Western and South Korean singleton samples (e.g. Cho et al, 2014;Sallis et al, 2000), this study showed that the prevalence of vigorous exercise was higher in males than in females. This study further showed that sex difference was driven largely by differences in the extreme groups (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…India scored a C for sedentary activity in its 2016 Report Card on Physical Activity, with only half of Indian children meeting sedentary behavior guidelines (Katapally et al, 2016). Given that sedentary behavior has been associated with childhood adiposity independent of physical activity (Cho, Lee, & Kim, 2014; Xue et al., 2016), it is important that policies and interventions aim at reducing time spent on sedentary activities while encouraging PA.…”
Section: Discussionmentioning
confidence: 99%
“…This confirmed what our HPE faculty have observed qualitatively for decades and conforms recent results from Cho, Lee, & Kim. 21 Thus it is not surprising that the relationship between Steps and BMI is better described by a quadratic model rather than linear one, see Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, individuals who are less physically active had higher maximum heart rates than those who were more active, indicative of increased cardiac workload. 20 Cho, Lee, & Kim 21 compared PA and sedentary behaviors with the BMI of Korean adolescent students. Using World Health Organization Asia-Pacific (AP) standards of obesity, it was found that significantly fewer students with a BMI of 18.5 kg · m -2 or lower (AP underweight) or 23.0 kg · m -2 and higher (AP overweight and obese) met the PA requirements than the students with a BMI between 18.5 kg · m -2 and 23.0 kg · m -2 (AP normal).…”
Section: Introductionmentioning
confidence: 99%